Islamic Economics Perspective on Coffee Farmers’ Product Quality, Digital Marketing, and Brand Image - Putri Hayati; Nurbaiti; Atika (Islamic Economics and finance in Focus, 2026)
This study aims to analyze coffee farmers’ perceptions of product quality, digital marketing, and brand image of Gayo coffee, and their impact on farmer welfare in the Islamic economic perspective in Southeast Aceh Regency. The background of this study is based on the gap between the theory of Islamic welfare (falah) and the actual reality experienced by coffee farmers, where despite producing approximately 15,000 tons of coffee per year, the average monthly income of farmers is only IDR 2–3 million. This study uses a qualitative descriptive approach with phenomenological methods, involving in-depth interviews with 20 coffee farmers in Southeast Aceh selected through purposive sampling. The results show that farmers’ perceptions of product quality are still limited to the raw processing stage, without adequate knowledge of post-harvest standards and halal certification. Digital marketing has not been optimally utilized due to low digital literacy and lack of structured promotional strategies. The brand image of local Gayo coffee has not been strongly established at the retail level. From an Islamic economic perspective, the existing marketing system has not reflected the principles of justice (‘adl), transparency (syafafiyah), and equitable distribution of benefits. This study contributes to the development of agribusiness studies based on Islamic economics and serves as the basis for formulating fairer and more sustainable coffee marketing strategies in Southeast Aceh.